The health condition of trees in dendropark at Faculty of Forestry – Skopje with a special focus on fungal diseases and insect pests - Papazova-Anakieva, Irena; Načeski, Sterja; Georgieva, Margarita (Šumarski list, 2022)
The Dendropark at the Faculty of Forestry in Skopje, North Macedonia, was established as an ‘outdoor museum’ with a collection of forest trees and shrub vegetation. The collection was planted in 1950 on the area of 4.05 ha, and includes 336 taxa from native Macedonian and Balkan endemic dendroflora and introduced species from around the world. The Dendropark, like the other botanical gardens all over the world, offers a unique resource that facilitate earlier detection of the potential invasive threats to forest tree species. The inventoried population includes 444 trees belonging to 43 families. The three most represented families are Pinaceae with 21 species (19.4%of the inventoried plants), Cupressaceae with 16 species (15.8%) and Rosaceae with 18 species (7.4%). The 2014 survey indicated that 33.8% of the total number of trees were rated with good health status, 1.8% as very good, 31.1% rated as fair, while 24.5% were poor. Approximately 4.1% were rated to be in a critical state (in a state of decline), and 4.7% of trees were dead. The assessment of health status of plants in the Dendropark could be used as a valuable asset to planners and decision makers and provides information about the quality, quantity and location of natural resources in urban areas. Identifying changes in plant species composition and presence of invasive pests and diseases helps maintaining healthy urban forests.
Keywords: Platanus orientalis L., powdery mildews, bark beetles